Uji Kinerja Mesin Pencacah Tipe GX 160 untuk Pencacahan Tongkol jagung dan Ampas Tebu - Muhammad Pijar; Siti Suharyatun; Mareli Telaumbanua; Agus Haryanto (Jurnal Agricultural Biosystem Engineering, 2022)
Agricultural waste is widely used as feed or a mixture of feed for livestock. Before use, agricultural waste must be chopped so that livestock can easily eat it. One of the agricultural waste chopping machines is a multipurpose type chopper. The aim of the research was to test the performance of a multipurpose chopper machine for chopping corn cobs and bagasse. This study used a completely randomized factorial design, consisting of 2 factors, namely material (corncob and sugarcane bagasse) and and the rotational speed (RPM) which consists of 600, 800, 1000 and 1360. Each treatment combination was repeated 3 times. Parameters observed were working capacity, weight loss, fuel consumption, specific fuel consumption, and fineness modulus. The results of this study indicate that the work capacity of the bagasse higher than corncob. Working capacity at speeds of 600 RPM to 1000 RPM will increase with increasing speed. Materials and RPM not effect to material loss. fuel consumption and specific fuel consumption of bagasse (0,859 lt/h; 0,074 lt/kg) are higher than corn cobs (0,754 lt/h; 0,170 lt/kg. Fineness modulus of corn cobs is 2.504% and sugarcane bagasse is 2.373%.